Meningkatkan Kesembuhan Pasien TB Paru Dengan Memberikan Dukungan Keluarga Dan Meningkatkan Motivasi Kesembuhan: Improving the Healing of Pulmonary TB Patients by Providing Family Support and Increasing Healing Motivation - Gumelar, Muhammad Agung (Indonesian Scholar Journal of Nursing and Midwifery Science, 2022)
Introduction: Globally, Indonesia ranks third out of eight countries that contributed the largest tuberculosis cases, accounting for 442,000 cases in 2017, and it is estimated that there are 8,600-15,000 MDR/RR TB. All patients who are confirmed to have pulmonary tuberculosis (TB) must undergo a long course of treatment, namely a minimum of six months of treatment, in which the first two months are the intensive phase and the next four months are latent or continuation phases, while undergoing a long treatment, the patient must have supporting factors to continue to undergo treatment regularly, including the motivation for healing from within the patient, and support from the family. Methods: This study is a quantitative analytical observational with a Cross-sectional approach. The sampling technique used was simple random sampling taken from all pulmonary TB patients at Dr. Goenawan Partowidigdo Cisarua Lung Hospital and produced as many as 30 respondents. The instruments used were two questionnaires, namely a recovery motivation questionnaire and a family support questionnaire, and an observation sheet used to observe the laboratory results of respondents' sputum smears. Results: The results of the study showed that from the results of the bivariate test between the motivation for recovery (p-value: 0.007), family support (p-value: 0,034), and the cure rate of pulmonary TB patients at Dr. Goenawan Partowidigdo Cisarua Lung Hospital. Discussion: There is a relationship between recovery motivation, family support and the cure rate of pulmonary TB patierts at Dr. Goenawan Partowidigdo Cisarua Lung Hospital.